ระบบเฝ้าสังเกตและหาเหตุแก้ไขข้อขัดข้องรถยนต์ผ่านโอบีดี 2 สแกนเนอร์ - วิชชุกร ฟูศรี (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Independent research, with the topic of Car Monitoring and Troubleshooting System via OBD 2 Scanner, is intended to investigate and develop an Android mobile application for notifying user about occurred car trouble and car maintenance information. Using the analyzed data, the system provides channel to car entrepreneurs to provide their services to customer when maintenance schedule is due or when their cars are facing the problems. Entrepreneurs can reach their target groups better using this provided system. Nevertheless, this development project consists of 5 groups of developers; there are manager, system analyst, system developer, tester and administrator. In addition, there are 6 documents are belonging to this project including Project Plan Requirements Specification Software Design Document User Acceptance Test Test Report and Software Maintenance Document The monitoring and troubleshooting system will be available in a mobile application that runs on Android OS. It connects to car via OBD2 scanner device in order to synchronize and analysis data. Moreover, the system provides car maintenance information to car entrepreneurs. In addition, the contains advertising system on web based application using Java Script Object Notation (JSON) technology will provide product and service according to occurring car trouble. All in this system for car monitoring and troubleshooting has been developed in accordance with ISO29110 to get quality software which meets the user’s need. According to the results of the Car Monitoring and Troubleshooting System via OBD 2 Scanner system test, the developed system can provide convenience to user for supplying car maintenance information in the aftermarket business. The system can represent the car information those are synchronized via OBD 2 scanner to allow car user realizing on the car trouble and maintenance plan. Besides, the car entrepreneurs can offer their products and services to their target customer groups.